Analisis Penerapan Sistem Informasi Pada Proses Bisnis Perusahaan Jasa: A Systematic Literature Review - Stefanie Mareta Angeline; Muhammad Shafiq Indrawan; Novanda Ramadhaniar (Lembaga Pengembangan Kinerja Dosen, 2023)
An information system is a collection of parts connected to one another in order to accomplish specific objectives. Information systems can be developed using a variety of tools, including waterfall, RAD, prototype, and many more. The purpose of this study is to examine how information systems are used in the world of service businesses. The information used for the study was sourced from Google Scholar, and the keyword